Perovskite oxide nanowire as well as preparation method and application thereof

CN119735242APending Publication Date: 2025-04-01华能张掖能源有限公司 +1
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202411974309.0
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-12-30
Publication Date
2025-04-01

AI Technical Summary

Technical Problem

The existing perovskite oxide catalysts have small specific surface area and few catalytic active sites, resulting in low catalytic activity.

Method used

A perovskite oxide nanowire with a diameter of 8 to 25 nm was used. Perovskite oxide nanowires with high specific surface area and multiple catalytic active sites were prepared by mixing carbon nanotubes, metal sources, complexing agents and solvents, and gelling reactions and annealing treatment.

Benefits of technology

The specific surface area and catalytic active sites of perovskite oxide nanowires are improved, their conductivity is enhanced, and better catalytic effects are achieved in the field of electrochemical catalysis.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119735242A_ABST
    Figure CN119735242A_ABST
Patent Text Reader

Abstract

The invention provides a perovskite oxide nanowire as well as a preparation method and application thereof. The diameter of the perovskite oxide nanowire is 8-25 nm, the perovskite oxide nanowire has a structure as shown in a general formula (I): ABO3 (I), A is selected from one or more of Sr and / or lanthanide elements, and B is selected from one or more of transition metal elements. Compared with a traditional blocky perovskite oxide catalyst, the perovskite oxide nanowire with the one-dimensional nanowire structure provided by the invention has the advantages of larger specific surface area, more catalytic active sites and more excellent conductivity, and can achieve a better catalytic effect when being applied to the field of electrochemical catalysis. The perovskite oxide nanowire with the specific diameter can be stacked to form a three-dimensional network structure, the mass transfer and electron transmission process is enhanced, and the perovskite oxide nanowire can be conveniently applied to the field of catalysis.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention relates to the technical field of nano material preparation, and in particular to a perovskite oxide nanowire, a preparation method and application thereof. Background Art

[0002] At present, researchers have conducted extensive and in-depth research in the field of electrocatalysis, such as water electrolysis for hydrogen production, electrochemical CO2 reduction, and electrochemical ammonia synthesis. They have tackled key issues such as catalytic materials and reaction systems, and have achieved certain results at the laboratory level. However, core catalytic materials often have one or more problems such as stability and economy, which leads to high technical costs and limits the progress of their large-scale application. Therefore, the development of efficient and stable catalytic materials is of great significance to electrocatalytic technology.

[0003] Perovskite oxide has a unique ABO3-type crystal structure, with AO layers and B-O2 layers cross-stacked, giving it good spatial tolerance and making it exhibit good stability. At the same time, its A-site element and B-site element composition are rich, and the elemental composition can be flexibly adjusted according to the target reaction. It has shown good catalytic performance in many reactions such as methane oxidation, oxygen evolution reaction (OER) and oxygen reduction reaction (ORR). However, the preparation of perovskite oxide usually requires a higher temperature to form a stable structure, is easy to form a block material, and has a small specific surface area, which limits its catalytic activity per unit mass.

[0004] Therefore, in order to improve the catalytic activity of perovskite oxides, new preparation methods need to be developed to obtain better catalytic performance by increasing their specific surface area. Summary of the invention

[0005] The main purpose of the present invention is to provide a perovskite oxide nanowire, a preparation method and application thereof, so as to solve the problem in the prior art that the perovskite oxide catalyst has a small specific surface area and few catalytic active sites, resulting in low catalytic activity.

[0006] In order to achieve the above-mentioned purpose, the present invention provides a perovskite oxide nanowire on the one hand, wherein the diameter of the perovskite oxide nanowire is 8 to 25 nm, and the perovskite oxide nanowire has a structure shown in the general formula (I): ABO3(I), wherein A is selected from one or more of Sr and / or lanthanide elements, and B is selected from one or more of transition metal elements.

[0007] Furthermore, the aspect ratio of the perovskite oxide nanowires is (20-200):1.

[0008] Furthermore, the specific surface area of ​​the perovskite oxide nanowires is 150 to 450 cm 2 / mg.

[0009] Furthermore, A is selected from one or more of the group consisting of Sr and / or La, Pr, Sm and Nd.

[0010] Furthermore, B is selected from one or more elements in Group VIIB and Group VIII, preferably one or more elements in the group consisting of Ni, Fe, Co and Mn.

[0011] In order to achieve the above-mentioned purpose, another aspect of the present invention further provides a method for preparing the above-mentioned perovskite oxide nanowires provided by the present application, the preparation method comprising: step S1, mixing carbon nanotubes, a metal source, a complexing agent and a solvent to obtain a mixed system; wherein the metal source comprises A metal salt and B metal salt, and the molar ratio of the A element in the A metal salt to the B element in the B metal salt is 1:(0.95~1.05); the diameter of the carbon nanotube is 5~20nm; step S2, subjecting the mixed system to a gelation reaction to obtain a precursor; step S3, annealing the mixed system in an oxygen-containing atmosphere to obtain perovskite oxide nanowires.

[0012] Furthermore, the A element is selected from one or more of the group consisting of Sr and / or La, Pr, Sm and Nd.

[0013] Furthermore, the B element is selected from one or more elements in Group VIIB and Group VIII, and is more preferably one or more elements in the group consisting of Ni, Fe, Co and Mn.

[0014] Furthermore, the A metal salt is selected from one or more of the group consisting of acetates, nitrates, hydrates of acetates and hydrates of nitrates containing the A element; further preferably, it is one or more of the group consisting of lanthanum acetate, lanthanum nitrate, strontium acetate and strontium nitrate, and / or one or more of the group consisting of hydrates of lanthanum acetate, lanthanum nitrate, strontium acetate and strontium nitrate.

[0015] Further, the B metal salt is selected from one or more of the group consisting of nitrates, chlorides, acetates, hydrates of nitrates, hydrates of chlorides and hydrates of acetates containing the B element; further preferably, it is one or more of the group consisting of nickel nitrate, nickel chloride, nickel acetate, ferric nitrate, ferric chloride, ferric acetate, cobalt nitrate, cobalt chloride, cobalt acetate, manganese nitrate and manganese chloride, and / or one or more of the group consisting of hydrates of nickel nitrate, nickel chloride, nickel acetate, ferric nitrate, ferric chloride, ferric acetate, cobalt nitrate, cobalt chloride, cobalt acetate, manganese nitrate and manganese chloride.

[0016] Furthermore, in the mixed system, the molar concentration of the A metal salt is 0.1 to 2 mol / L.

[0017] Furthermore, in the mixed system, the molar ratio of the A element in the A metal salt to the complexing agent is 1:(2-4).

[0018] Furthermore, in the mixed system, the mass concentration of the carbon nanotubes is 0.1 to 1.5 mg / mL.

[0019] Furthermore, the complexing agent is selected from one or more of the group consisting of citric acid, ethylenediaminetetraacetic acid and disodium ethylenediaminetetraacetic acid.

[0020] Furthermore, the temperature of the gelation reaction is 70 to 100°C.

[0021] Furthermore, the gelation reaction includes two stages. The first stage is carried out under shear conditions, preferably at 5000-20000 rpm, for a processing time of 1-5 min. The second stage is carried out under stirring conditions, preferably at 200-500 rpm, for a processing time of 20-50 min.

[0022] Further, step S1 includes: mixing carbon nanotubes with a portion of the solvent to obtain a carbon nanotube dispersion; mixing a metal source, a complexing agent and the remaining portion of the solvent to obtain a metal salt dispersion; mixing the carbon nanotube dispersion with the metal salt dispersion to obtain a mixed system.

[0023] Furthermore, the mass concentration of the carbon nanotube dispersion is 0.1 to 1.5 mg / mL.

[0024] Furthermore, the solvent is selected from a mixed solvent of alcohol and water, preferably a mixed solvent of ethylene glycol, lower alcohol and water, wherein the lower alcohol is selected from one or more of the group consisting of isopropanol, propanol, ethanol and methanol, and the volume percentage of ethylene glycol in the solvent is preferably ≤8 vol%, and the volume ratio of ethylene glycol to lower alcohol is 1:(1-10).

[0025] Furthermore, the annealing treatment includes a programmed heating stage and a cooling stage, wherein the programmed heating stage includes: heating to 400-500°C at a heating rate of 5-20°C / min, keeping warm for 60-120min, then heating to 600-800°C at a rate of 5-10°C / min, keeping warm for 120-600min, and the cooling stage includes: cooling to 20-30°C at a rate of 5-25°C / min.

[0026] Furthermore, the carbon nanotubes used in step S1 are modified carbon nanotubes, and the preparation method of the modified carbon nanotubes includes: step SA-1, mixing unmodified carbon nanotubes with an aqueous hydrogen peroxide solution to obtain a suspension; step SA-2, filtering and washing the suspension to obtain a solid substance; step SA-3, dispersing the solid substance in a nitric acid solution, or a mixture of sulfuric acid and hydrogen peroxide and performing a modification treatment to obtain modified carbon nanotubes.

[0027] Furthermore, the mass concentration of the hydrogen peroxide aqueous solution is 10 to 30 wt %.

[0028] Furthermore, in the suspension, the mass concentration of the unmodified carbon nanotubes is 0.1-2 mg / mL.

[0029] Furthermore, the mixing temperature in step SA-1 is 60 to 90° C., and the mixing time is 10 to 50 minutes.

[0030] Furthermore, the molar concentration of the nitric acid solution is 8 to 15 mol / L.

[0031] Furthermore, the temperature of the modification treatment is 100-150° C., and the time is 4-8 hours.

[0032] Another aspect of the present invention provides an application of the perovskite oxide nanowires provided in the present application in the field of electrochemical catalysis.

[0033] By applying the technical solution of the present invention, the above-mentioned perovskite oxide nanowires provided in the present application have a structure shown in the general formula (I), wherein the Sr element, or the lanthanide element, or the Sr element and the lanthanide element jointly occupy the A site, and the transition metal element occupies the B site. Compared with other types of elements, the use of the above-mentioned types of A and B can exert the catalytic activity of the perovskite oxide nanowires. Moreover, compared with the traditional bulk perovskite oxide catalyst, the above-mentioned perovskite oxide nanowires with a one-dimensional nanowire structure provided in the present application have a larger specific surface area, more catalytic active sites, and also have better electrical conductivity, and their application in the field of electrochemical catalysis can achieve better catalytic effects. In addition, the perovskite oxide nanowires with the above-mentioned specific diameter can be stacked to form a three-dimensional network structure, enhance mass transfer and electron transport processes, and are convenient for application in the field of catalysis. BRIEF DESCRIPTION OF THE DRAWINGS

[0034] The drawings constituting a part of the present application are used to provide a further understanding of the present invention. The exemplary embodiments of the present invention and their descriptions are used to explain the present invention and do not constitute an improper limitation of the present invention. In the drawings:

[0035] Figure 1 TEM image of LaCoO3 nanowires prepared in Example 1 is shown;

[0036] Figure 2 The electrolysis performance test curves of the LaCoO3 nanowires prepared in Example 1 and the LaCoO3 nanoparticles prepared in Comparative Example 1 as electrodes are shown;

[0037] Figure 3 The electrochemical impedance test curves of the LaCoO3 nanowires prepared in Example 1 and the LaCoO3 nanoparticles prepared in Comparative Example 1 are shown;

[0038] Figure 4 The electrochemical surface area test curves of the LaCoO3 nanowires prepared in Example 1 and the LaCoO3 nanoparticles prepared in Comparative Example 1 are shown. DETAILED DESCRIPTION

[0039] It should be noted that, in the absence of conflict, the embodiments and features in the embodiments of the present application can be combined with each other. The present invention will be described in detail below in conjunction with the embodiments.

[0040] As described in the background art, the existing perovskite oxide catalysts have a small specific surface area and few catalytic active sites, resulting in low catalytic activity. In order to solve the above technical problems, the first aspect of the present application provides a perovskite oxide nanowire, the diameter of the perovskite oxide nanowire is 8 to 25 nm, and the perovskite oxide nanowire has a structure shown in the general formula (I): ABO3 (I), wherein A is selected from one or more of Sr and / or lanthanide elements, and the B element is selected from one or more of transition metal elements.

[0041] The above-mentioned perovskite oxide nanowires provided in the present application have a structure shown in the general formula (I), wherein the Sr element, or the lanthanide element, or the Sr element and the lanthanide element jointly occupy the A site, and the transition metal element occupies the B site. Compared with other types of elements, the use of the above-mentioned types of A and B can exert the catalytic activity of the perovskite oxide nanowires. Moreover, compared with the traditional bulk perovskite oxide catalyst, the above-mentioned perovskite oxide nanowires with a one-dimensional nanowire structure provided in the present application have a larger specific surface area, more catalytic active sites, and also have better electrical conductivity, and their application in the field of electrochemical catalysis can achieve better catalytic effects. In addition, the perovskite oxide nanowires with the above-mentioned specific diameter can be stacked to form a three-dimensional network structure, enhance mass transfer and electron transport processes, and are convenient for application in the field of catalysis.

[0042] In a preferred embodiment, the aspect ratio of the perovskite oxide nanowire is (20-200): 1. The aspect ratio of the perovskite oxide nanowire includes but is not limited to the above range, and limiting it within the above range is conducive to increasing the specific surface area of ​​the perovskite oxide nanowire, thereby increasing the catalytic active sites and further improving its catalytic activity.

[0043] The specific surface area of ​​the perovskite oxide nanowires provided in the present application is relatively high. In a preferred embodiment, the specific surface area of ​​the perovskite oxide nanowires is 150 to 450 cm 2 / mg.

[0044] In a preferred embodiment, A includes but is not limited to Sr and / or one or more of the group consisting of La, Pr, Sm and Nd. A in the general formula (I) includes but is not limited to the above types, and limiting it to the above types is beneficial to improving the structural stability of the perovskite oxide nanowires and facilitating their performance in catalytic reactions.

[0045] In a preferred embodiment, B includes but is not limited to one or more elements in Group VIIB and Group VIII. Compared with other types, the use of the above types of B is conducive to improving the electrochemical catalytic activity of the perovskite oxide nanowires, improving the conductivity of the perovskite oxide nanowires, and facilitating their performance in catalytic reactions.

[0046] In order to further improve the catalytic activity and conductivity of the perovskite oxide nanowires, preferably, B includes but is not limited to one or more of the group consisting of Ni, Fe, Co and Mn.

[0047] The second aspect of the present application also provides a method for preparing the above-mentioned perovskite oxide nanowires provided by the present application, and the preparation method comprises: step S1, mixing carbon nanotubes, a metal source, a complexing agent and a solvent to obtain a mixed system; wherein the metal source comprises A metal salt and B metal salt, and the molar ratio of the A element in the A metal salt to the B element in the B metal salt is 1:(0.95~1.05); the diameter of the carbon nanotube is 5~20nm; step S2, subjecting the mixed system to a gelation reaction to obtain a precursor; step S3, annealing the mixed system in an oxygen-containing atmosphere to obtain perovskite oxide nanowires.

[0048] In the above-mentioned preparation method provided by the present application, carbon nanotubes can be used as templates to regulate the microstructure of the product due to their tubular structure. During the gelation reaction, the complex products formed by the metal source and the complexing agent are gathered inside the carbon nanotubes, and undergo thermal decomposition reaction in the subsequent annealing treatment to obtain perovskite oxide nanowires, and the carbon nanotubes are converted into carbon dioxide and removed during the annealing treatment. Compared with other ranges, limiting the diameter of the carbon nanotubes to the above range can physically confine the product of the reaction of the metal source and the complexing agent in the carbon nanotube tube, thereby obtaining perovskite oxide nanowires of a specific diameter.

[0049] Compared with other ranges, limiting the molar ratio of the A element in the A metal salt to the B element in the B metal salt within the above range can make the prepared perovskite oxide nanowires have the structure shown in the general formula (I), thereby improving its catalytic activity.

[0050] Compared with traditional bulk perovskite oxide catalysts, the perovskite oxide nanowires with a one-dimensional nanowire structure prepared by the above-mentioned preparation method of the present application have a larger specific surface area, more catalytic active sites, and better conductivity. Applying them in the field of electrochemical catalysis can achieve better catalytic effects.

[0051] In a preferred embodiment, the A element includes but is not limited to Sr and / or one or more of the group consisting of La, Pr, Sm and Nd. The A element includes but is not limited to the above-mentioned types, and limiting it within the above-mentioned type range facilitates the formation of perovskite oxide nanowires, is conducive to the formation of perovskite oxides with more stable structures, and is conducive to the product to more stably exert catalytic performance.

[0052] In a preferred embodiment, the B element includes but is not limited to one or more elements in Group VIIB and Group VIII. The B element includes but is not limited to the above-mentioned types, and limiting it within the above-mentioned types is convenient for forming a perovskite oxide with good electrochemical catalytic activity components, which is beneficial to improving the conductivity of the perovskite oxide nanowires, thereby facilitating its catalytic effect and facilitating its application in the field of catalysis.

[0053] In order to further improve the catalytic activity and conductivity of the perovskite oxide nanowires, preferably, the B element includes but is not limited to one or more of the group consisting of Ni, Fe, Co and Mn.

[0054] In a preferred embodiment, the A metal salt includes but is not limited to one or more of the group consisting of acetate, nitrate, acetate hydrate and nitrate hydrate containing element A; further preferably, one or more of the group consisting of lanthanum acetate, lanthanum nitrate, strontium acetate and strontium nitrate, and / or one or more of the group consisting of hydrates of lanthanum acetate, lanthanum nitrate, strontium acetate and strontium nitrate. Compared with other types, the use of the above-mentioned types of A metal salts can provide the elements required for the A site, and the raw materials of the above-mentioned A metal salts are easy to obtain, have good dispersibility in the solvent, and are easy to mix.

[0055] In a preferred embodiment, the B metal salt includes but is not limited to one or more of the group consisting of nitrates, chlorides, acetates, hydrates of nitrates, hydrates of chlorides and hydrates of acetates containing the B element; further preferably, one or more of the group consisting of nickel nitrate, nickel chloride, nickel acetate, ferric nitrate, ferric chloride, ferric acetate, cobalt nitrate, cobalt chloride, cobalt acetate, manganese nitrate and manganese chloride, and / or one or more of the group consisting of hydrates of nickel nitrate, nickel chloride, nickel acetate, ferric nitrate, ferric chloride, ferric acetate, cobalt nitrate, cobalt chloride, cobalt acetate, manganese nitrate and manganese chloride. Compared with other types, the use of the above-mentioned types of B metal salts can provide the elements required for the B site, and the raw materials of the above-mentioned B metal salts are easy to obtain, have good dispersibility in the solvent, and are easy to mix.

[0056] In a preferred embodiment, in the mixed system, the molar concentration of the metal salt A is 0.1 to 2 mol / L. The molar concentration of the metal salt A includes but is not limited to the above range, and limiting it within the above range is conducive to improving the uniformity of the composition of the subsequently prepared perovskite oxide nanowires, thereby facilitating the improvement of the catalytic activity of the perovskite oxide nanowires.

[0057] In a preferred embodiment, in the mixed system, the molar ratio of the A element in the A metal salt to the complexing agent is 1:(2-4). The molar ratio of the metal source to the complexing agent includes but is not limited to the above range, and limiting it within the above range is beneficial to improving the utilization rate of raw materials, the reaction efficiency of the gelation reaction, and the generation rate of the precursor, thereby improving the yield of the perovskite oxide nanowires.

[0058] In order to improve the utilization rate of the template and the yield of perovskite oxide nanowires, preferably, the mass concentration of carbon nanotubes in the mixed system is 0.1-1.5 mg / mL.

[0059] In a preferred embodiment, the complexing agent includes but is not limited to one or more of the group consisting of citric acid, ethylenediaminetetraacetic acid (EDTA) and ethylenediaminetetraacetic acid disodium salt (EDTA-2Na). The use of the above-mentioned complexing agents is beneficial to improving the reaction efficiency of the A metal salt, the B metal salt and the precursor, thereby improving the yield of the perovskite oxide nanowires.

[0060] In a preferred embodiment, the temperature of the gelation reaction is 70-100° C. The temperature of the gelation reaction includes but is not limited to the above range, and limiting it within the above range is conducive to improving the reaction efficiency of the gelation reaction, and is conducive to forming a more uniform precursor in the nanotubes, thereby facilitating the formation of a perovskite oxide with more uniform components and more stable structure.

[0061] In a preferred embodiment, the gelation reaction includes two stages, the first stage is carried out under shearing conditions, more preferably under 5000-20000rpm conditions, and the processing time is 1-5min, and the second stage is carried out under stirring conditions, more preferably under 200-500rpm conditions, and the time is 20-50min. The above process conditions are conducive to improving the reaction efficiency of the gelation reaction and improving the uniformity of the dispersion of each ion in the precursor inside the carbon nanotube.

[0062] In a preferred embodiment, step S1 includes: mixing carbon nanotubes with a portion of the solvent to obtain a carbon nanotube dispersion; mixing a metal source, a complexing agent and the remaining portion of the solvent to obtain a metal salt dispersion; and mixing the carbon nanotube dispersion with the metal salt dispersion to obtain a mixed system. The above mixing method is conducive to improving the dispersibility of the carbon nanotubes and the dispersibility of the metal source, thereby facilitating the subsequent gelation reaction and making the reaction more complete.

[0063] In order to further improve the dispersibility of carbon nanotubes in the solvent, preferably, the mass concentration of the carbon nanotube dispersion is 0.1-1.5 mg / mL.

[0064] In order to improve the dispersibility of raw materials such as carbon nanotubes and metal sources in the solvent, increase the viscosity of the precursor, and form good encapsulation in the carbon nanotubes, preferably, the solvent includes but is not limited to a mixed solvent of alcohol and water, and is further preferably a mixed solvent of ethylene glycol, lower alcohol and water, wherein the lower alcohol includes but is not limited to one or more of the group consisting of isopropanol, propanol, ethanol and methanol.

[0065] In order to further improve the dispersibility of raw materials such as carbon nanotubes and metal sources in the solvent and improve the encapsulation degree of the sol-gel in the precursor within the carbon nanotubes, preferably, the volume percentage of ethylene glycol in the solvent is ≤8 vol%, and the volume ratio of ethylene glycol to lower alcohol is 1:(10~1).

[0066] In a preferred embodiment, the annealing treatment includes a programmed temperature rise stage and a temperature drop stage, wherein the programmed temperature rise stage includes: heating to 400-500°C at a heating rate of 5-20°C / min, keeping the temperature for 60-120min, then heating to 600-800°C at a rate of 5-10°C / min, keeping the temperature for 120-600min, and the temperature drop stage includes: cooling to 20-30°C at a rate of 5-25°C / min. Compared with other annealing treatment processes, the use of the above-mentioned range of heating rate, holding temperature and time is conducive to improving the decomposition efficiency of the precursor, improving the yield and purity of the perovskite oxide nanowires, and also helping to improve the diameter uniformity of the perovskite oxide nanowires, thereby helping to improve their specific surface area, catalytic activity and conductivity.

[0067] In a preferred embodiment, the carbon nanotubes used in step S1 are modified carbon nanotubes, and the preparation method of the modified carbon nanotubes includes: step SA-1, mixing unmodified carbon nanotubes with aqueous hydrogen peroxide solution to obtain a suspension; step SA-2, filtering and washing the suspension to obtain a solid substance; step SA-3, dispersing the solid substance in a nitric acid solution or a mixed solution of sulfuric acid and hydrogen peroxide and performing a modification treatment to obtain a modified carbon nanotube. The above-mentioned modification treatment of unmodified carbon nanotubes in the above-mentioned manner is conducive to opening up the tubular channels of the carbon nanotubes, facilitating the subsequent enrichment of the reaction products of the metal salt and the complexing agent in the tube, and is also conducive to increasing the content of oxygen-containing functional groups on the surface of the carbon nanotubes (especially the inner wall surface), thereby facilitating the enrichment of the reaction products of the metal salt and the complexing agent in the tube, improving the yield of the precursor, and further facilitating the uniformity of the diameter of the perovskite oxide nanowires, thereby facilitating the improvement of its specific surface area, catalytic activity and conductivity.

[0068] In order to further improve the modification effect on the unmodified carbon nanotubes, preferably, the mass concentration of the hydrogen peroxide aqueous solution is 10 to 30 wt %.

[0069] In order to improve the dispersibility of the unmodified carbon nanotubes, preferably, the mass concentration of the unmodified carbon nanotubes in the suspension is 0.1-2 mg / mL.

[0070] In a preferred embodiment, the mixing temperature in step SA-1 is 60-90°C and the mixing time is 10-50 minutes. The mixing temperature and time in step SA-1 include but are not limited to the above ranges, which are beneficial to improving the modification effect on the unmodified carbon nanotubes.

[0071] In order to further improve the modification effect on the unmodified carbon nanotubes, preferably, the molar concentration of the nitric acid solution is 8 to 15 mol / L.

[0072] In order to further improve the modification effect on the unmodified carbon nanotubes, preferably, the modification temperature is 100-150° C. and the time is 4-8 hours.

[0073] The third aspect of the present application also provides an application of the above-mentioned perovskite oxide nanowires provided by the present application in the field of electrochemical catalysis. Compared with the traditional bulk perovskite oxide catalyst, the above-mentioned perovskite oxide nanowires with a one-dimensional nanowire structure provided by the present application have a larger specific surface area, more catalytic active sites, and also have better conductivity, and their application in the field of electrochemical catalysis can achieve better catalytic effects.

[0074] The present application is further described in detail below in conjunction with specific embodiments. These embodiments should not be construed as limiting the scope of protection claimed in the present application.

[0075] Example 1

[0076] A method for preparing perovskite oxide LaCoO3 nanowires, comprising:

[0077] (1) 100 mg of carbon nanotubes (CNTs, with a tube diameter of 15 to 20 nm and a length of 1 to 3 μm) were mixed with 100 mL of a 20 wt% hydrogen peroxide solution and stirred at 80° C. for 30 min, and then the solid was filtered out and washed three times with deionized water. The solid was then added to 100 mL of a 10 mol / L concentrated nitric acid solution and stirred at 120° C. for 5 h for modification. The modified carbon nanotubes were then washed with deionized water and ethanol, and then filtered out to obtain the modified carbon nanotubes.

[0078] (2) dispersing 48 mg of the modified carbon nanotubes in 60 mL of a mixed solvent (the volume ratio of water, ethanol and ethylene glycol in the mixed solvent is 10:3:1) to obtain a carbon nanotube dispersion; mixing 43.3 mg of lanthanum nitrate hexahydrate and 29.2 mg of cobalt nitrate hexahydrate with 100 mL of a mixed solvent (the volume ratio of water, ethanol and ethylene glycol in the mixed solvent is 9:3:1), adding 40 mg of citric acid after complete dissolution, stirring to form a clear solution (i.e., a metal salt dispersion), and mixing the clear solution with the carbon nanotube dispersion to obtain a mixed system;

[0079] (3) using a high-speed shear force instrument to treat the mixed system at a rotation speed of 15,000 rpm for 2 min, then stirring at 80° C. for 50 min to perform a gelation reaction, and filtering to obtain a precursor;

[0080] (4) The precursor is annealed in an oxygen atmosphere, firstly heated to 480°C at a rate of 5°C / min, maintained for 90 min, then heated to 700°C at a rate of 8°C / min, maintained for 400 min, and then cooled to room temperature at a rate of 10°C / min to obtain perovskite oxide LaCoO3 nanowires.

[0081] like Figure 1 As shown in the TEM image, the perovskite oxide LaCoO3 prepared in Example 1 has a one-dimensional nanowire structure with a diameter of 20 nm, an aspect ratio of (20-200):1, an average aspect ratio of 80:1, and a specific surface area of ​​385 cm 2 / mg.

[0082] Example 2

[0083] The difference from Example 1 is that the diameter of the carbon nanotubes is 5 nm.

[0084] The diameter of the LaCoO3 nanowires prepared in Example 2 is 6 nm.

[0085] Example 3

[0086] The difference from Example 1 is that the diameter of the carbon nanotubes is 20 nm.

[0087] The diameter of the LaCoO3 nanowires prepared in Example 3 is 22 nm.

[0088] Example 4

[0089] The difference from Example 1 is that the diameter of the carbon nanotubes is 3 nm.

[0090] The diameter of the LaCoO3 nanowires prepared in Example 4 is 4 nm.

[0091] Example 5

[0092] The difference from Example 1 is that the molar concentration of lanthanum nitrate hexahydrate in the mixed system of step (2) is 0.1 mol / L.

[0093] Example 6

[0094] The difference from Example 1 is that the molar concentration of lanthanum nitrate hexahydrate in the mixed system of step (2) is 2 mol / L.

[0095] Example 7

[0096] The difference from Example 1 is that the molar concentration of lanthanum nitrate hexahydrate in the mixed system of step (2) is 5 mol / L.

[0097] Example 8

[0098] The difference from Example 1 is that the mass concentration of modified carbon nanotubes in the mixed system in step (2) is 0.1 mg / mL.

[0099] Example 9

[0100] The difference from Example 1 is that the mass concentration of modified carbon nanotubes in the mixed system in step (2) is 1.5 mg / mL.

[0101] Example 10

[0102] The difference from Example 1 is that the mass concentration of modified carbon nanotubes in the mixed system in step (2) is 2.0 mg / mL.

[0103] Embodiment 11

[0104] The difference from Example 1 is that the temperature of the gelation reaction in step (3) is 70°C.

[0105] Example 12

[0106] The difference from Example 1 is that the temperature of the gelation reaction in step (3) is 100°C.

[0107] Embodiment 13

[0108] The difference from Example 1 is that the temperature of the gelation reaction in step (3) is 50°C.

[0109] Embodiment 14

[0110] A method for preparing perovskite oxide SrCoO3, comprising:

[0111] (1) The modification process of carbon nanotubes is exactly the same as step (1) of Example 1;

[0112] (2) dispersing 48 mg of the modified carbon nanotubes in 60 mL of a mixed solvent (the volume ratio of water, ethanol and ethylene glycol in the mixed solvent is 11:3:1) to obtain a carbon nanotube dispersion; mixing 21.2 mg of strontium nitrate hexahydrate and 29.2 mg of cobalt nitrate hexahydrate with 100 mL of a mixed solvent (the volume ratio of water, ethanol and ethylene glycol in the mixed solvent is 9:3:1), adding 20 mg of citric acid after complete dissolution, stirring to form a clear solution (i.e., a metal salt dispersion), and mixing the clear solution with the carbon nanotube dispersion to obtain a mixed system;

[0113] (3) using a high-speed shear force instrument to treat the mixed system at a rotation speed of 15,000 rpm for 2 min, then stirring at 80° C. for 50 min to perform a gelation reaction, and filtering to obtain a precursor;

[0114] (4) The precursor is annealed in an oxygen atmosphere, firstly heated to 460°C at a rate of 5°C / min, maintained for 90 min, then heated to 680°C at a rate of 8°C / min, maintained for 400 min, and then cooled to room temperature at a rate of 10°C / min to obtain perovskite oxide SrCoO3 nanowires.

[0115] The diameter of the perovskite oxide SrCoO3 nanowires was measured to be 17 nm, the aspect ratio was 15:180, and the specific surface area was 347 cm 2 / mg.

[0116] Comparative Example 1

[0117] The difference from Example 1 is that no carbon nanotubes are introduced into the mixed system in step (2).

[0118] The perovskite oxide LaCoO3 prepared in Comparative Example 1 has a granular structure, and its average particle size is 200 nm.

[0119] Comparative Example 2

[0120] The difference from Example 14 is that no carbon nanotubes are introduced into the mixing system in step (2).

[0121] The perovskite oxide SrCoO3 prepared in Comparative Example 1 has a granular structure, and its average particle size is 320 nm.

[0122] The nanowires prepared in the examples of the present application and the nanoparticles prepared in the comparative example were made into slurries and coated on one side of a nickel felt (Shengerno, thickness 400 μm, porosity 80%), with a coating amount of 2.5 mg / cm 2 The cathode in the AEM (anion exchange membrane) electrolyzer is a 40wt% Pt / C@carbon paper catalytic electrode, and the anion exchange membrane is an Aemion produced by IonomrInnovations Inc. TM , with a thickness of 75μm, at 1A / cm 2 The water electrolysis performance test and electrochemical impedance test were carried out at a current density of 1 mol / L KOH and the test temperature was 60°C.

[0123] The nanowires prepared in the examples of the present application and the nanoparticles prepared in the comparative example were respectively dropped on the surface of a 5 mm glassy carbon electrode as a working electrode, and the electrochemical surface area test was performed using a capacitance method in a three-electrode system. In the three-electrode system, the reference electrode was a mercury-mercury oxide electrode, the counter electrode was a platinum wire, the electrolyte was 1 mol / L KOH, and the test temperature was 25°C.

[0124] The test results are shown in Table 1.

[0125] Table 1

[0126] Overpotential(V) Charge transfer impedance (mΩ) <![CDATA[Capacitance method slope (mF / cm 2 )]]> Example 1 1.84 30 1.62 Example 2 1.84 33 1.65 Example 3 1.85 34 1.62 Example 4 1.89 40 1.51 Example 5 1.85 33 1.61 Example 6 1.85 34 1.60 Example 7 1.91 44 1.50 Example 8 1.86 33 1.58 Example 9 1.85 33 1.61 Example 10 1.92 45 1.32 Embodiment 11 1.86 36 1.54 Example 12 1.85 35 1.57 Embodiment 13 1.93 47 1.33 Embodiment 14 1.86 37 1.58 Comparative Example 1 1.94 63 0.87 Comparative Example 2 1.97 68 0.85

[0127] The electrolysis performance test curves of the LaCoO3 nanowires prepared in Example 1 and the LaCoO3 particles prepared in Comparative Example 1 as electrodes are shown in FIG. Figure 2 As shown. Figure 2 It can be seen that at 1A / cm 2 At a current density of 1.54 V, the overpotentials of the two were 1.84 V and 1.94 V, respectively, which indicates that LaCoO3 nanowires have higher catalytic activity than LaCoO3 particles.

[0128] The electrochemical impedance test curves of the LaCoO3 nanowires prepared in Example 1 and the LaCoO3 nanoparticles prepared in Comparative Example 1 are as follows: Figure 3 As shown. Figure 3 It can be seen that the conductivity of LaCoO3 nanowires is significantly better than that of LaCoO3 nanoparticles.

[0129] The electrochemical surface area test curves of the LaCoO3 nanowires prepared in Example 1 and the LaCoO3 nanoparticles prepared in Comparative Example 1 are as follows: Figure 4 As shown. Figure 4 It can be seen that the electrochemical surface area of ​​LaCoO3 nanowires is higher than that of LaCoO3 nanoparticles.

[0130] From the above description, it can be seen that the above embodiments of the present invention achieve the following technical effects:

[0131] The above-mentioned perovskite oxide nanowires provided in the present application have a structure shown in the general formula (I), wherein the Sr element, or the lanthanide element, or the Sr element and the lanthanide element jointly occupy the A site, and the transition metal element occupies the B site. Compared with other types of elements, the use of the above-mentioned types of A and B can exert the catalytic activity of the perovskite oxide nanowires. Moreover, compared with the traditional bulk perovskite oxide catalyst, the above-mentioned perovskite oxide nanowires with a one-dimensional nanowire structure provided in the present application have a larger specific surface area, more catalytic active sites, and also have better electrical conductivity, and their application in the field of electrochemical catalysis can achieve better catalytic effects. In addition, the perovskite oxide nanowires with the above-mentioned specific diameter can be stacked to form a three-dimensional network structure, enhance mass transfer and electron transport processes, and are convenient for application in the field of catalysis.

[0132] It should be noted that the terms "first", "second", etc. in the specification and claims of the present application are used to distinguish similar objects, and are not necessarily used to describe a specific order or sequence. It should be understood that the terms used in this way can be interchangeable where appropriate, so that the embodiments of the present application described herein can be implemented in an order other than those described herein, for example.

[0133] The above description is only a preferred embodiment of the present invention and is not intended to limit the present invention. For those skilled in the art, the present invention may have various modifications and variations. Any modification, equivalent replacement, improvement, etc. made within the spirit and principle of the present invention shall be included in the protection scope of the present invention.

Claims

1. A perovskite oxide nanowire, characterized in that: The diameter of the perovskite oxide nanowire is 8 to 25 nm, and the perovskite oxide nanowire has a structure shown in the general formula (I): ABO3(I), wherein A is selected from one or more of Sr and / or lanthanide elements, and B is selected from one or more of transition metal elements.

2. The perovskite oxide nanowire according to claim 1, characterized in that: The aspect ratio of the perovskite oxide nanowire is (20-200):1; Preferably, the specific surface area of ​​the perovskite oxide nanowires is 150 to 450 cm 2 / mg; Preferably, A is selected from one or more of the group consisting of Sr and / or La, Pr, Sm and Nd; Preferably, B is selected from one or more elements in Group VIIB and Group VIII, and more preferably one or more elements in the group consisting of Ni, Fe, Co and Mn.

3. A method for preparing perovskite oxide nanowires according to claim 1 or 2, characterized in that: The preparation method comprises: Step S1, mixing carbon nanotubes, a metal source, a complexing agent and a solvent to obtain a mixed system; wherein the metal source comprises an A metal salt and a B metal salt, and the molar ratio of the A element in the A metal salt to the B element in the B metal salt is 1:(0.95-1.05); and the diameter of the carbon nanotubes is 5-20 nm; Step S2, subjecting the mixed system to a gelation reaction to obtain a precursor; Step S3, annealing the mixed system in an oxygen-containing atmosphere to obtain the perovskite oxide nanowires.

4. The method for preparing perovskite oxide nanowires according to claim 3, characterized in that: The A element is selected from one or more of the group consisting of Sr and / or La, Pr, Sm and Nd; Preferably, the B element is selected from one or more elements in Group VIIB and Group VIII, and more preferably one or more elements in the group consisting of Ni, Fe, Co and Mn; Preferably, the A metal salt is selected from one or more of the group consisting of acetates, nitrates, hydrates of acetates and hydrates of nitrates containing the A element; further preferably, it is one or more of the group consisting of lanthanum acetate, lanthanum nitrate, strontium acetate and strontium nitrate, and / or one or more of the group consisting of hydrates of lanthanum acetate, lanthanum nitrate, strontium acetate and strontium nitrate; Preferably, the B metal salt is selected from one or more of the group consisting of nitrates, chlorides, acetates, hydrates of nitrates, hydrates of chlorides and hydrates of acetates containing the B element; further preferably, it is one or more of the group consisting of nickel nitrate, nickel chloride, nickel acetate, ferric nitrate, ferric chloride, ferric acetate, cobalt nitrate, cobalt chloride, cobalt acetate, manganese nitrate and manganese chloride, and / or one or more of the group consisting of hydrates of nickel nitrate, nickel chloride, nickel acetate, ferric nitrate, ferric chloride, ferric acetate, cobalt nitrate, cobalt chloride, cobalt acetate, manganese nitrate and manganese chloride.

5. The method for preparing perovskite oxide nanowires according to claim 3 or 4, characterized in that: In the mixed system, the molar concentration of the metal salt A is 0.1 to 2 mol / L; Preferably, in the mixed system, the molar ratio of the A element in the A metal salt to the complexing agent is 1:(2-4); Preferably, in the mixed system, the mass concentration of the carbon nanotubes is 0.1 to 1.5 mg / mL; Preferably, the complexing agent is selected from one or more of the group consisting of citric acid, ethylenediaminetetraacetic acid and disodium ethylenediaminetetraacetic acid.

6. The method for preparing perovskite oxide nanowires according to any one of claims 3 to 5, characterized in that: The temperature of the gelation reaction is 70-100°C; Preferably, the gelation reaction includes two stages, the first stage is carried out under shear conditions, more preferably at 5000-20000 rpm, and the processing time is 1-5 min, and the second stage is carried out under stirring conditions, more preferably at 200-500 rpm, and the time is 20-50 min.

7. The method for preparing perovskite oxide nanowires according to claim 6, characterized in that: The step S1 comprises: mixing the carbon nanotubes with a portion of the solvent to obtain a carbon nanotube dispersion; mixing the metal source, the complexing agent and the remaining part of the solvent to obtain a metal salt dispersion; Mixing the carbon nanotube dispersion with the metal salt dispersion to obtain the mixed system; Preferably, the mass concentration of the carbon nanotube dispersion is 0.1 to 1.5 mg / mL; Preferably, the solvent is selected from a mixed solvent of alcohol and water, and more preferably is a mixed solvent of ethylene glycol, lower alcohol and water, wherein the lower alcohol is selected from one or more of the group consisting of isopropanol, propanol, ethanol and methanol, and further preferably, the volume percentage of ethylene glycol in the solvent is ≤8 vol%, and the volume ratio of ethylene glycol to the lower alcohol is 1:(1-10).

8. The method for preparing perovskite oxide nanowires according to claim 7, characterized in that: The annealing treatment includes a programmed heating stage and a cooling stage, wherein the programmed heating stage includes: heating to 400-500°C at a heating rate of 5-20°C / min, keeping the temperature for 60-120min, then heating to 600-800°C at a rate of 5-10°C / min, keeping the temperature for 120-600min, and the cooling stage includes: cooling to 20-30°C at a rate of 5-25°C / min.

9. The method for preparing perovskite oxide nanowires according to any one of claims 3 to 7, characterized in that: The carbon nanotubes used in step S1 are modified carbon nanotubes, and the preparation method of the modified carbon nanotubes includes: Step SA-1, mixing unmodified carbon nanotubes with an aqueous hydrogen peroxide solution to obtain a suspension; Step SA-2, filtering and washing the suspension to obtain a solid substance; Step SA-3, dispersing the solid substance in a nitric acid solution or a mixture of sulfuric acid and hydrogen peroxide and performing a modification treatment to obtain the modified carbon nanotubes; Preferably, the mass concentration of the aqueous hydrogen peroxide solution is 10 to 30 wt %; Preferably, in the suspension, the mass concentration of the unmodified carbon nanotubes is 0.1 to 2 mg / mL; Preferably, the mixing temperature in step SA-1 is 60 to 90° C. and the mixing time is 10 to 50 min; Preferably, the molar concentration of the nitric acid solution is 8 to 15 mol / L; Preferably, the temperature of the modification treatment is 100-150° C. and the time is 4-8 hours.

10. Use of the perovskite oxide nanowire according to claim 1 or 2 in the field of electrochemical catalysis.